Successful Video-Assisted Thoracoscopic Surgery Following Neoadjuvant Chemoimmunotherapy for Stage IIIB Central Squamous Cell Lung Cancer: A Case Report - Zinchenko, E. I.; Petrov, A. S.; Fateeva, D. L.; Pischik, V. G. (Innovacionnaâ medicina Kubani (Online), 2025)
When surgical treatment is limited in patients with stage IIIA-IIIB non–small cell lung cancer (NSCLC), multimodality treatment can improve long-term outcomes: neoadjuvant chemotherapy to reduce the tumor size followed by radical surgery. In recent years, the combination of standard induction chemotherapy with immune checkpoint inhibitors has been the subject of active debate in the literature. Some studies demonstrate the efficacy of neoadjuvant chemoimmunotherapy, whereas other authors note additional difficulties of surgery after it. In this case report we demonstrate features of surgery in a male patient with stage IIIB central NSCLC after chemoimmunotherapy and discuss difficulties of surgery associated with a minimally invasive video-assisted thoracoscopic surgery approach in complex anatomical lung resection and methods for preventing intraoperative and postoperative complications.